Analysis of Traffic Volume and Frequency of Vannamei Shrimp (Litopenaeus vannamei) Shipments Based on a Certification Approach - Octovianus; Mahendri Rohman Ghanim; Artanti Tri Lestari; R Adharyan Islamy (Jurnal Penelitian Pendidikan IPA, 2023)
Volume and frequency of shipping are crucial factors that impact the profitability and sustainability of the vannamei shrimp industry. This study aims to determine the volume of vannamei shrimp shipping traffic in Padangbai, Karangasem, Bali during the period 2019-2021 and the relationship between the volume of vannamei shrimp shipping traffic and shipping times during that period in the region. Data were obtained from fish quarantine stations, quality control and fishery product safety in Padangbai, Karangasem, Bali. The analytical method is carried out in a comparative descriptive manner which is presented through graphs that have been processed in the MS program. Excel while to find out the relationship between volume and frequency of shipping was analyzed using regression. The volume of traffic for shipping vannamei shrimp out of the Padangbai area, Karangasem, Bali was highest in 2021 (652,745,431 Juvenils) and lowest in 2019 (435,740,234 Juvenils). Data on the frequency of traffic was highest in 2020 (383 times) and lowest in 2019 (268 times). Based on the data provided, it can be seen that the average total vannamei shrimp shipment during the 2019-2021 period was around 4,702 x 104 juveniles per month. There were fluctuations in shipment volume from month to month, where in February, March, August, September and December the highest shipments were recorded of more than 5,000 x 104 juveniles, while in other months the lowest shipments were recorded of 2,929 x 104 juveniles in June. Based on these data, it can be concluded that the volume of vannamei shrimp shipments from Padangbai, Karangasem, Bali is quite stable with relatively small fluctuations. Even though there are fluctuations in shipping volume from month to month, overall, the volume of vannamei shrimp shipments from Padangbai, Karangasem, Bali is quite high.